2015
DOI: 10.4081/monaldi.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of CURB-65 and Pneumonia Severity Index for Influenza A H1N1v pneumonia

Abstract: Use of CURB-65 and PSI in the emergency department may underestimate the risk of patients with Influenza A H1N1v pneumonia. Based in our results, the ability of these scales to predict ICU admissions for Influenza A H1N1v pneumonia is questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Though it has been previously demonstrated that PSI ≥ class IV indicates increased disease severity and is strongly associated with ICU admission [28,29], our results show that PSI scores cannot be used to accurately prognosticate viral CAPs. Furthermore, literature suggests that PSI often underestimates the risk of patients with Influenza A H1N1 pneumonia [30,31] and neither PSI nor CURB-65 scores can be used to predict ICU admission or need for mechanical ventilation in influenza patients31. The CDC recommends early antiviral therapy for patients who are suspected of suffering from influenza [32].…”
Section: Discussionmentioning
confidence: 99%
“…Though it has been previously demonstrated that PSI ≥ class IV indicates increased disease severity and is strongly associated with ICU admission [28,29], our results show that PSI scores cannot be used to accurately prognosticate viral CAPs. Furthermore, literature suggests that PSI often underestimates the risk of patients with Influenza A H1N1 pneumonia [30,31] and neither PSI nor CURB-65 scores can be used to predict ICU admission or need for mechanical ventilation in influenza patients31. The CDC recommends early antiviral therapy for patients who are suspected of suffering from influenza [32].…”
Section: Discussionmentioning
confidence: 99%
“…Commons and Denholm investigated 105 patients of H1N1 influenza infection and found that the common used CAP severity scores (PSI and CURB‐65) had insufficient predictive ability to low‐risk patients in ICU admission. Other researches also showed that routine prediction rules underestimated severity of influenza A 2009 (H1N1) Pneumonia, but no effective severity score had been put forward. In our study, PSI and CURB‐65 underestimated a significant number of hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported the use of different prognostic scales of pneumonia to evaluate influenza [39][40][41][42][43][44]. Myles et al [39] compared the performance of Community Assessment Tools (CATs), CURB-65 score, and the Pandemic Medical Early Warning Score in influenza.…”
Section: Discussionmentioning
confidence: 99%
“…However, theirs was a case-control study and was limited to H1N1 infections, which might have conferred some bias. Another retrospective study used eight different scoring tools, including CURB-65, Mortality in Emergency Department Sepsis (MEDS) score, the Nursing Home-Acquired Pneumonia score, PMEWS, Pneumonia Severity Index, severity score for the elderly with community-acquired pneumonia score, SMART-COP Score, and Simple Triage Scoring System, to predict the outcomes of influenza in the ED [40,43]. These researchers found that the PSI and MEDS scores were moderately predictive of inhospital mortality, and the SMARTCOP score was a good predictor of ICU admission.…”
Section: Discussionmentioning
confidence: 99%